Vocational Skills Education to Grow the Junior High School Students’ Work Intention - Murniati, Titi; Tentama, Fatwa; Santosa, Budi (Journal of Vocational Education Studies, 2020)
The purpose of this study was to find out what vocational skills education was implemented in SMP Muhammadiyah Majenang, a private junior high school in Cilacap, Central Java, and to find out how to develop vocational skills education to foster the students’ entrepreneurial intention. It is expected that this vocational skill can foster entrepreneurial intention to the students themselves early, to make them the young entrepreneurs. This research was a research and development with a qualitative approach. Research and development were modified from the ten steps of Borg and Gall, consisting of three stages, namely: preliminary study, model development, and model testing. Participants involved included the principal, representative of the curriculum deputy, teachers, advisers, and students. The data collection techniques used questionnaires, observation, interviews, and document studies. The results of the study found the existence of extracurricular activities in the form of self-development game activities. Self-development game is indicated by the achievement in certain fields. The results of the development found that the existence of agricultural extracurricular activities in the form of chili cultivation could foster the students’ entrepreneurial intentions. We found that the positive attitudes and abilities of entrepreneurship were possessed by students, including selling chili crops and chili seeds to the general public. The program for developing extracurricular activities also produces vocational skills in the form of students who independently plant seeds other than chili and inspire students to sell other seeds.